(untitled) (Herald of Journalism, 2018)
The author of the article analyzes network journalism in the modern world as a multimedia activity, reveals media features in the Internet space, explains the properties of information perception. Describes the 4 principles of communication and the diversity of information. Then, it reveals the types of analysis, the essence of the method, and the content on the Internet.